HAIR TONIC FORMULATION OF CLOVE LEAVES (SYZYGIUM AROMATICUM) ETHANOL EXTRACT AND THE EFFECTIVENESS ON RABBIT HAIR GROWTH - ABADI, HAFIZHATUL; WINATA, HANAFIS SASTRA; PARHAN; DIANA, VIVI EULIS; CHAN, ADEK; HARYANI, RENY (International Journal of Applied Pharmaceutics, 2020)
Objective: The purpose of this study was to determine the physical stability and effectiveness of hair growth in hair tonic preparations containing ethanol extract of clove leaves (Syzygium aromaticum) with a concentration variation of 5, 10, and 15%. Methods: Formulations were evaluated, including organoleptic observation, pH checking, and preparation stability tests using the Climatic Chamber. The effectiveness of clove leaf extract as a hair tonic was tested by looking at hair growth in test animals. Results: The results showed that the preparation was stable at high temperatures (40±2 °C) where the odor, color, clarity, and pH remained constant. Effectiveness test on rabbit hair growth showed significantly different results after measuring hair growth on the 21st day, where the results were 11.83+0.06 mm for positive control, 1.71+0.06 mm as blank, 1.69+0.06 mm for the group without treatment, and successively the results of the group given clove leaf extract 5, 10, and 15% were 4.00+0.06; 4.80+0.06; and 5.46+0.08 mm. Conclusion: Hair tonics containing clove ethanol extract can increase rabbit hair growth.